Numerical simulation of phase change at high hydrostatic pressure under variable-gravity environment - Kowalczyk, Wojciech; Delgado, Antonio (Numerical Heat Transfer Part A-Applications, 2007)
We present a numerical investigation of phase change of water at high hydrostatic pressure conditions occurring under a gravitational environment and a low-gravity environment. A computational model consists of conservation equations of mass, momentum, and energy. Phase-transition phenomena are modeled with an enthalpy-porosity approach. Numerical solutions are obtained for process stages dominated by free convection as well as by forced convection. A high pressure-assisted freezing / thawing is carried out in the pressure range from the ambient pressure up to 150MPa. Differences in the thermofluid dynamics observed in the high-pressure chamber operated under gravity and low-gravity conditions are discussed. The results reveal significant influence of gravity on the distribution of temperature and velocity and consequently on the different ice growth characteristics.
UnivIS-Import:2015-03-09:Pub.2007.tech.ITC.stmmec.numeri